MRI Findings of Periarticular Lesions with Isolated Greater Tubercle Fractures and Dislocation - Yoon, Yu Sung; Cha, Jang Gyu (Current Medical Imaging, 2023)
Purpose: To identify MRI findings for injuries to periarticular soft tissue structures that were related to isolated greater tubercle fracture. Materials and Methods: 16 patients (mean age: 53.8, range 30-71 yrs) were enrolled and diagnosed with isolated greater tubercle (GT) fracture with CT and MRI and underwent shoulder arthroscopy from September 2009 to April 2019. Two musculoskeletal radiologists were blinded to the patient history and arthroscopic surgical findings and reviewed patient’s CT and MRI. Fracture displacement, fracture center, and presence of bony Bankart lesion with Hill sachs lesion were checked on shoulder CT. Soft tissue injuries, including rotator cuff injury, deltoid muscle injury, long head of biceps tendon injury, capsular injury, glenoid injury, and injury location of the subscapularis and infraspinatus were checked on shoulder MRI. Results: MRI showed supraspinatus injury (56.3%), subscapularis injury (56.3%), deltoid muscle injury (25%), infraspinatus injury (25%), teres minor muscle injury (37.5%), injury of the long head of the biceps tendon (43.8%), inferior glenohumeral ligament tear (87.5%), superior labral anterior-toposterior lesion (25%), Bankart lesion (18.8%), and Hill-Sachs lesion (6.3%). 88.9% of subscapularis injuries and 75% of infraspinatus injuries showed caudal predominance. All of the patients with infraspinatus injuries showed concomitant teres minor muscle injuries. In order of frequency, the fracture centers were anterior (25%), posterior (31.3%), and all (43.8%). For patients with Bankart and Hill- Sachs lesions, the fracture center included the posterior portion in all cases. Conclusion: MRI and active arthroscopic examinations may be valuable when an isolated GT avulsion fracture is identified on X-ray examination.
Keywords: injuries